Hazard Identification and Risk Assessment (Hira) Analysis of Nanotechnology Laboratory in Universities in Indonesia - Kustono, Djoko; Puspitasari, Poppy; Irsyad, Muhammad Al; Nursabrina, Aisya; Adesta, Erry Yulian Triblas (International Journal of Mechanical Engineering Technologies and Applications, 2021)
The article describes a concept of health and safety to conduct research in Nanomaterial Laboratory in Two Public University in Malang, East Java, Indonesia. The utilization of nanomaterials in the world of education has been done in two universities in Malang, namely Malang State University and Brawijaya University. The nanomaterial laboratory as a means for research and development of nanomaterial science that often creates hazards and risks of work accidents for its users, but things that are often not realized. Dangers and risks of work accidents caused by the absence of standards. This research focuses on hazards and accidents in the nanomaterial laboratory using the HIRA (Hazard Identification and Risk Assessment) method, which is then followed by a variety of independent variables. The population in this study were nanomaterial researchers at two universities in Malang. Based on the results of trials between respondents 'competency expertise with the level of risk of workplace accidents in the nanomaterial laboratory obtained p- value 0.00 (<0.05), meaning that there is a significant relationship between the respondents' scientific conservation and the level of work accident risk in the nanomaterials laboratory. Furthermore, the results of the study were also obtained between the research respondents with the level of risk of work accidents in the nanomaterial laboratory with a p-value of 0.00 (<0.05), meaning that there was a significant correlation between the respondent's research experience and the level of work accident risk in the nanomaterial laboratory.